Residual limb fluid volume change and volume accommodation: Relationships to activity and self-report outcomes in people with trans-tibial amputation - Sanders, Joan E (Prosthet Orthot Int, 2018)
STUDY DESIGN: Standardized, two-part laboratory protocol with an interim observational period. BACKGROUND: Fluctuations in limb volume degrade prosthesis fit and require users to accommodate changes using management strategies, such as donning or doffing prosthetic socks. OBJECTIVES: To examine how activities and self-reported outcomes relate to daily changes in residual limb fluid volume and volume accommodation. METHODS: Participants were classified as “accommodators” or “non-accommodators,” based on self-report prosthetic sock use. Participants’ residual limb fluid volume change was measured using a custom bioimpedance analyzer and a standardized in-laboratory activity protocol. Self-report health outcomes were assessed with the Socket Comfort Score and Prosthesis Evaluation Questionnaire. Activity was monitored while participants left the laboratory for at least 3 hours. They then returned to repeat the bioimpedance test protocol. RESULTS: Twenty-nine people were enrolled. Morning-to-afternoon percent limb fluid volume change per hour was not strongly correlated to percent time weight-bearing or to self-report outcomes. As a group, non-accommodators (n=15) spent more time with their prosthesis doffed and reported better outcomes than accommodators. CONCLUSIONS: Factors other than time weight–bearing may contribute to morning-to-afternoon limb fluid volume changes and reported satisfaction with the prosthesis among trans-tibial prosthesis users. Temporary doffing may be a more effective and satisfying accommodation method than sock addition.